BRIDGING THE INTERNATIONAL GAP: THE ROLE OF NATIONAL HUMAN RIGHTS INSTITUTIONS IN THE IMPLEMENTATION OF HUMAN RIGHTS TREATIES IN AFRICA - Aliyu Ibrahim (Obiter, 2018)
While most of the United Nations (UN) treaties have committees to monitor the implementation of their provisions among their States parties, one of the major challenges they encounter is their inability to independently verify the information provided by the States parties, on the level of fulfilling their obligations to the treaties. However, the establishment of National Human Rights Institutions (NHRIs) by the majority of UN member states was meant to not only promote and protect human rights within the territories of States parties, but also to monitor the implementation of the provisions of treaties at the domestic level. This resulted in treaty bodies to encourage NHRIs, in monitoring and providing it with information on the level of implementation of the provisions of these treaties within the territories of respective States parties. This article examines whether these institutions in Africa have been able to discharge their mandates concerning the implementation of two treaties, namely, the International Covenant on Civil and Political Rights (ICCPR) which is monitored by the Human Rights Committee (HRC) and the International Covenant on Economic, Social and Cultural Rights (ICESCR) which is overseen by the Committee on Economic, Social and Cultural Rights (CESCR). The NHRIs of South Africa, Morocco and Nigeria have been selected to test the effectiveness of these institutions. The study ultimately shows that the majority of these institutions are still far off from achieving their potential.